1962
DOI: 10.1007/bf03158561
|View full text |Cite
|
Sign up to set email alerts
|

Negative absorption coefficient at indirect transitions in semiconductors

Abstract: In this paper a method for obtaining states with negative temperature in semiconductors is discussed; as shown this method requires relatively small densities of excitation.Ac present three different methods ate proposed for obtaining the states with negative temperatures in semiconductors [1--3]. The impulse method put forward in the paper [1] for obtaining such states is based on a considerable difference of the time of recombination and the slowing-down time of nonequilibrium carriers in the bands [4]. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…For this reason, blowing of the gunpowder gases, which affects mainly on the surface friction, effects slightly on the total resistance of the gunpowder grains for the incoming flow. Experimentally, this fact was confirmed in [6,7], where it is shown that since Re σ > 10 3 correction for blowing can be ignored.…”
Section: λσmentioning
confidence: 64%
“…For this reason, blowing of the gunpowder gases, which affects mainly on the surface friction, effects slightly on the total resistance of the gunpowder grains for the incoming flow. Experimentally, this fact was confirmed in [6,7], where it is shown that since Re σ > 10 3 correction for blowing can be ignored.…”
Section: λσmentioning
confidence: 64%
“…N. G. Basov, who proposed crystals of inert gases as a VUV-laser medium in 1966, 4 depended on the successful use of the electron-beam method 5 that he had proposed in 1961 to pump lasers based on broad-band semiconductor crystals, first implemented on cadmium sulfide crystals in 1964 at FIAN. 6 An experimental technique had already been prepared and studies had been carried out on the properties of semiconductor crystals at low temperatures: 350-58 K (liquid nitrogen), 4.2-1.08 K (liquid He4), and 3.3-0.35 K (liquid He3) by the time studies began on the electronic pumping of VUV lasers based on inert-gas crystals.…”
Section: Introductionmentioning
confidence: 99%